Alcoholic beverages : Sensory evaluation and consumer research - Piggott, J. (Woodhead Publishing in food science, technology, and nutrition, 2011)
Sensory evaluation methods are extensively used in the wine, beer and distilled spirits industries for product development and quality control. Consumer research methods are also significant. This book explores key research and practice in these areas.